A multisensory phenomenology of interrail mobilities. (July 2015) - Jensen, Martin Trandberg; Scarles, Caroline; Cohen, Scott A.
Highlights: Demonstrates how multisensory phenomenology can inform tourism mobilities research. Examines influences of rhythms, sounds and temperatures on interrail experiences. Combines audio-visual impressionistic tales and netnography to tourism research. Develops the concept 'thermalscapes' to inform sensuous tourism research. Abstract: This paper suggests that phenomenological studies of tourism mobilities can be informed by non-representational approaches. We extend recent developments in sensory tourism research and non-representational works to argue that methods upon which tourism researchers have long relied require 'pushing' or merging in previously underutilised ways that support these emerging areas of study. As a result, this paper embraces embodied methodologies. It integrates audio-visual impressionistic tales and netnographic snippets to shape its multisensory exploration of an under-researched European tourism and train travel phenomenon, interrailing. Our analysis exemplifies how the rhythmscapes and soundscapes of everyday rail travel inform the experience of interrail. Finally, we introduce the concept of thermalscapes, giving attention to the relatively neglected role of temperatures in tourism experiences.